Construction of a model for corporate sustainability assessment: a case study in the textile industry - Zamcopé,Fábio Cristiano (2012)
Due to the increasing pressure for companies to become more accountable and transparent regarding their actions, the stakeholders have been provided with information beyond the scope of company's financial performance including evidence of good corporate governance, source of raw material, the manufacturing process, and life cycle of the products. Business leaders have recognized the need to respond to these pressures by conducting operations focusing on the business success and meeting stakeholders' demands. Accordingly, in this study, a model for assessment of corporate sustainability was constructed considering the company's need to seek business longevity. Therefore, a case study was carried out in a medium sized textile industry in Paraná state adopting the Multicriteria Methodology for Decision Aid - Constructivist as the intervention tool. This methodology was chosen because it makes it possible to identify a set of performance indicators that characterize the company sustainability and to measure the organization properties and its commitment to sustainability, both individually and globally. The model identified that the company's strategy should include all the criteria of the economic, social, and environmental areas demonstrating that the differences between the replacement rates are strictly small. Furthermore, the model revealed that the actions of communication with the stakeholders are of great importance and that a lot of effort is needed in terms of awareness of employees, suppliers, customers, consumers, and the community of sustainability issues.